Neurosurgical applications of radiotherapy. Issue 8 (August 2021) - Soldá, Francesca; Tancu, Cornel; Kitchen, Neil; Fersht, Naomi
Abstract: The term 'radiosurgery' (RS) indicates a high precision localized technique of irradiation used as an alternative to surgical excision in patients with malignant or benign conditions, both in the brain and in the body. Brain RS has been historically identified with 'stereotactic radiotherapy'. The term refers to the long-established neurosurgical technique of localizing the position of a lesion in the brain by using a system of external 3D co-ordinates coupled with rigid head immobilization device (often fixed to the skull). A high dose of radiation is delivered to the target stereotactically identified and a safe and accurate treatment is achieved, minimizing the dose of radiation to the surrounding brain. While for some techniques the traditional stereotactic localization has been replaced by the integration of modern imaging with non-invasive accurate immobilization, the term 'stereotactic' is still maintained in the clinical practice. Over the past 30 years, the implementation of powerful diagnostic imaging devices and of new radiotherapy equipment has contributed to the large diffusion of brain RS. RS plays an important role in the management of brain tumours, vascular and functional brain lesions and the expertise of the multidisciplinary treating team (clinical oncologists, neurosurgeons, neuro-radiologists and medical physics) contributes to the treatment success rate.